Development of Hybrid Learning Multimedia Assisted by Telegram in Modern Physics - Yeni Megalina; Rugaya Rugaya; Juniar Hutahaean; Rajo Hasim Lubis (Jurnal Penelitian Pendidikan IPA, 2023)
After the covid 19 period ended, learning at Medan State University was conducted face-to-face and online, creating good learning media and design is part of the effort to achieve learning objectives effectively as mandated by the education system. This study aims to develop hybrid learning multimedia assisted by telegram, which is feasible, practical and makes students independent and influential. The research was conducted at the Physics Department of State University of Medan. The phases that will be carried out during the research are needs analysis, design of learning multimedia, development and validation of learning multimedia, implementation of multimedia to students, and internal and external evaluation. The resulting product is a learning multimedia that will be applied to partners, namely students of the Physics Department who take Modern Physics courses. This multimedia was sent to the Telegram group class of 2021 B and 2021 C students. The results of this study are: (a) the percentage of assessment scores for learning multimedia from material experts is 81% and the percentage of assessment scores from media experts is 83% (b) the percentage of student independence questionnaires is 83.8% (c) the percentage of student practicality questionnaires is 88.2% (d) N-gain for PSPF 2021-B is obtained, the result obtained is 0.23 because N-gain <0.23 in the low category and N-gain for PSPF 2021-C is obtained, the result obtained is 0.3 in the medium category.